Reconnoitering the Core Parallels Concerning the Perception of Divinity and Eastern Ethics among Taoism , Buddhism and Hinduism - Muhammad Asad Latif (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research aims to explore the idea of divinity in eastern religions, including Taoism, Hinduism, and so on, and then find commonalities between these religions and this notion. This essay seeks to understand why Eastern traditions deviated from the worship of God and how their conception of divinity came to be. This research is significant because it sheds light on the prevalent beliefs in China and India, which include the worship of ancestors who are fathers and grandfathers, the sanctification of natural forces, the belief in the plurality of deities, and the practice of spiritual worship to achieve the state of union with God. The purpose of this study is to provide answers to the following questions: Is the eastern conception of divinity unified? The research relied on the mother of all texts of eastern beliefs, the Tao, and employed both the inductive and the deductive methods. The study's most significant conclusions are that belief in the monotheistic concept of deity is not the foundation of the ethical and philosophical eastern religions that are most prevalent in China and India. The study also revealed that Eastern beliefs met a plurality of gods, and that people gradually went through stages in their quest to find the god who best suited their needs. They also practiced magic, sorcery, astrology, and other forms of polytheism, as well as worshiping the forces of nature, totems, and humans.